ENHANCING STUDENT ENGAGEMENT THROUGH DIGITAL TOOLS IN TEACHING LEXICAL CHUNKS - Aksulu Kudaybergenova; Satibaldieva Nigora Alimqul qizi (Modern American Journals, 2025)
This study explores how digital tools can enhance student engagement in the teaching of lexical chunks in English as a foreign language classroom. Lexical chunks—multi-word units such as collocations, idioms, and phrasal verbs—are essential for achieving fluency and naturalness in language use. However, students often find them difficult to retain and use correctly. Through a synthesis of recent pedagogical research (Lewis, 1993; Nation, 2001; Schmitt, 2000) and practical classroom observations, this paper examines how digital platforms such as Quizlet, Kahoot, and interactive mobile apps (Godwin-Jones, 2011; Wang, 2015) can increase learner motivation, participation, and retention. The findings suggest that integrating technology into vocabulary instruction not only supports personalized and contextualized learning but also fosters greater engagement through interactive, game-based, and collaborative activities.
Keywords: digital tools, student engagement, lexical chunks, vocabulary learning, language teaching, educational technology